2007
DOI: 10.1242/jcs.03455
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilis toxin stimulates intestinal epithelial cell shedding and γ-secretase-dependent E-cadherin cleavage

Abstract: Enterotoxigenic Bacteroides fragilis – organisms that live in the colon – secrete a metalloprotease toxin, B. fragilis toxin. This toxin binds to a specific intestinal epithelial cell receptor and stimulates cell proliferation, which is dependent, in part, on E-cadherin degradation and β-catenin–T-cell-factor nuclear signaling. γ-Secretase (or presenilin-1) is an intramembrane cleaving protease and is a positive regulator of E-cadherin cleavage and a negative regulator of β-catenin signaling. Here we examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(119 citation statements)
references
References 52 publications
3
108
0
2
Order By: Relevance
“…We also observe a similar cleavage product in response to staurosporine in MCF-7 and MDCK epithelial cells. Recently, Bacteroides fragilis toxin was also reported to stimulate ␥-secretase-induced cleavage of E-cadherin (52). However, the physiological stimuli that induce the production of E-cad/CTF2 were not clear.…”
Section: Discussionmentioning
confidence: 99%
“…We also observe a similar cleavage product in response to staurosporine in MCF-7 and MDCK epithelial cells. Recently, Bacteroides fragilis toxin was also reported to stimulate ␥-secretase-induced cleavage of E-cadherin (52). However, the physiological stimuli that induce the production of E-cad/CTF2 were not clear.…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular interest as enteric pathogens, such as E. coli and Campylobacter, can increase mucosal permeability during the acute phase of the infection [41][42][43]. In addition, recent genetic studies have identified a link between variants in the same region of the gene, as found in this study, with susceptibility to colorectal cancer [44], ulcerative colitis [45] and Crohn's disease [46].…”
Section: Discussionmentioning
confidence: 69%
“…Internalin A from Listeria monocytogenes [43,44] and invasion Als3 from Candida albicans interact with E-cadherin to allow the internalization of the respective microorganisms. The metalloproteinase toxin BFT from Bacteroides fragilis was shown to induce the shedding of the E-cadherin ectodomain through an unknown IEC receptor-mediated induction of g-secretase [45]. Also trypsin-like serine protease HpHtrA from Helicobacter pylori can produce E-cadherin cleavage.…”
Section: Gut Microbiota Sustains Intestinal Damagementioning
confidence: 99%